2017
DOI: 10.1021/acsami.7b11784
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Simple and Easily Accessible Perylenes for Dye-Sensitized Solar Cells Applicable to Both 1 Sun and Dim-Light Environments

Abstract: The need for low-cost and highly efficient dyes for dye-sensitized solar cells under both the sunlight and dim light environments is growing. We have devised GJ-series push-pull organic dyes which require only four synthesis steps. These dyes feature a linear molecular structure of donor-perylene-ethynylene-arylcarboxylic acid, where donor represents N,N-diarylamino group and arylcarboxylic groups represent benzoic, thienocarboxylic, 2-cyano-3-phenylacrylic, 2-cyano-3-thienoacrylic, and 4-benzo[c][1,2,5]thiadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…Yeh and coworkers developed a series of dyes based on a substituted perylene light absorbing unit with different anchoring groups, all with absorption maxima about 550 nm. 49 Two of their dyes, GJ-P and GJ-BP, obtained similar results under T5 CF and LED lamps, with power outputs varying between 9 mW cm À2 at 300 lx and 276 mW cm À2 at 6000 lx. Chen et al presented a series of different dyes, all with D-p-A structure, especially designed for indoor applications, together with some discussion on general structural design strategies for indoor dyes.…”
Section: Sensitizersmentioning
confidence: 78%
“…Yeh and coworkers developed a series of dyes based on a substituted perylene light absorbing unit with different anchoring groups, all with absorption maxima about 550 nm. 49 Two of their dyes, GJ-P and GJ-BP, obtained similar results under T5 CF and LED lamps, with power outputs varying between 9 mW cm À2 at 300 lx and 276 mW cm À2 at 6000 lx. Chen et al presented a series of different dyes, all with D-p-A structure, especially designed for indoor applications, together with some discussion on general structural design strategies for indoor dyes.…”
Section: Sensitizersmentioning
confidence: 78%
“…Therefore, DSSCs are very competitive to the first and second generations of solar cells due to numerous advantages including easy fabrication, low cost (Figure 1) [3], and high performance at dim-light condition. Moreover, DSSCs can be used in indoor ambient applications [5][6][7][8][9].…”
Section: Dye-sensitized Solar Cells (Dsscs)mentioning
confidence: 99%
“…Presently, efficiencies over 25% have been achieved using the I − /I 3 − redox system. [14][15][16][17][18][19] In recent years, many studies have paid attention to employing the copper and cobalt redox-couple for the purpose of increasing cell efficiency. [20][21][22][23][24][25] Two typical studies were reported by the groups of Gratzel and Freitag, respectively, in 2018 and 2020.…”
Section: Introductionmentioning
confidence: 99%